An overview of the genetics of cervical cancer. (2018)
Cervical cancer is the fourth most common cancer in women, and the seventh of all human cancers. It is the most rampant cancer of the female genital tract in the developing world and manifests in two common histological subtypes: squamous cell carcinoma which is derived from squamous cells of the cervix and cervical adenocarcinoma which arose from the glandular cells. Most cases of deaths from cervical cancer occur in the less developed countries of the world where there are ineffective screening systems. Factors that increase the risk for developing cervical cancer include infection by Human Papilloma Virus (HPV) as the main direct factor and other indirect factors such as smoking, dietary habits, age, race, socioeconomic status, sexual history, use of oral contraceptives, high parity and the human immunodeficiency virus infection. Identifying the genetic alterations that predispose to or associate with cervical cancer will help in the screening of patients at risk of the cancer thereby allowing early diagnosis and prompt management with better outcomes. In this review we describe the role of HPV DNA integration into the host cellular genome, the effects of viral E6 and E7 proteins, and the loss of heterozygosity as genetic factors in cervical cancer.